Ecologia alimentar e reprodutiva de Nannopterum brasilianum Gmelin, 1789 (Aves: Phalacrocoracidae): interações tróficas com pescarias no Sistema Estuarino de Laguna, Santa Catarina, Brasil - Pimenta, Victor Ribeiro Alvares (Universidade Federal de São Carlos, 2024)
The Neotropic cormorant (Nannopterum brasilianum) is an abundant psicivorous bird within its distribution area, especially inside Brazil. Despite its wide ocurrence, the bird ecological aspects are yet not explored by South american scientists. In Laguna Estuarine System (SEL), localized at southern coast of Santa Catarina State, Brazil, tradicional fishing community express nuances of a potential increase in cormorant population and its feeding habitats. This thesis evaluates the species ecological aspects of a populated dormitory at SEL. We assess cormorant population dinamics, diet, estuarine spatial use and reproduction from 2021 to 2023. The region is economically, culturally and historically important to South of Brazil and supports an intense fishing activity, demanding evidence-based evaluation of the interactions between cormorants and fishing resources. Diet analisys revealed diversified and generalists feeding habits, with cormorants consuming pelagic and demersal fishes composed mainly by the next families Ariidae, Engraulidae, Scianidae, Gerreidae e Atherinopsidae. Through otolith analisys sampled by regurgitated pellets, we assessed mean prey sizes of 128,6 +67,6mm and a diary consumption of biomass of 382,2 ±23,5g. Population counts indicated peaks of abundance during autumn and winter, corresponding to the establishment of reprodutive colonies in Laguna adjancies. By direct observations and the utilization of biologgers we observed maximum travel distances of 18 km to feeding areas, but mostly travels ocurred near the dormitory/colony (Nóca Lagoon). We observed a peak of 2780 nests and a reproductive sucess of 56,9% in 2023 colony located at Nóca Lagoon. Here we also document the first conflict between N. brasilianum and artisanal fisheries in Brazil. With ilegal actions and lesgislative responses, exemplified by ordinary law n° 2.154/ 2020. Yet, the conflict lacks evidence-based data and demand holistic and interdisciplinar approaches to its resolution or mitigation of possible negative outputs to biodiversity conservation and sustainable use of natural resources.
Feeding and reproductive ecology of Nannopterum brasilianum Gmelin, 1789 (Aves:Phalacrocoracidae): trophic interactions with artisanal fisheries from Laguna Estuarine System, Santa Catarina, Brasil
Keywords: Ave aquática; Biguá; Dieta; Reprodução; Sustentabilidade; Aquatic bird; Neotropic cormorant; Diet; Reproduction; Sustainability; CIENCIAS BIOLOGICAS::ECOLOGIA; CIENCIAS BIOLOGICAS::ZOOLOGIA